Сутність спадкової трансмісії у спадковому праві України - Кухарєв, О. Є.; Kukharev, O. Y.; ORCID: http://orcid.org/0000-0003-2086-9179 (Вісник Національної академії правових наук України. - 2015. - № 2 (81). - С. 73-81, 2015)
У статті досліджується сутність спадкової трансмісії у спадковому праві України. Визначаються особливості механізму переходу права на прийняття спадщини. Розглянуто питання про можливість розширення об’єкта спадкової трансмісії.

This article examines the legal nature of hereditary transmission in inheritance law of Ukraine. The peculiarities of the mechanism of the transition the right to inheritance are defned. Special attention is paid to the subject of hereditary transmission. Positions expressed in the legal literature regarding the classifcation of hereditary transmission as: the type of inheritance by law; separate grounds of inheritance, different from inheritance under the will and according to the law; the case of singular succession of inheritance are criticized. It is emphasized, that in case of transfer of the inheritance right by way of hereditary transmission, there is a special case of generic hereditary succession, where there is another party to the relationship – transmitent – between the legal predecessor and the successor. Unlike the classic transfer of rights and obligations of the testator to the heirs without the involvement of any other entities. It is stressed that in recent years in the legal literature the trend towards expansion of grounds (types) of the inheritance defned by civil law. The types of inheritance include, in particular, inheritance by right of representation, hereditary transmission; the inheritance of the right to a compulsory share of inheritance; hereditary contract. The paper identifes the following conditions of transfer of ownership on the adoption of heritage to transmissar: 1) the death of the testator; 2) calls for inheritance of the heir-transmitent. In this case the type of the inheritance does not matter; 3) the death of the heir-transmitent after the death of the testator, but before the expiration of the period for acceptance of the inheritance. That is to say the death heir-transmitent must occur within six months from the day following the day of the testator’s death; 4) the right of inheritance or its refusal was not exercised by transmitent after the death of the testator; 5) transmitent has a successor (transmissar), which is called to inheritance after the death of transmitent; 6) transmissar has exercised his right to inheritance, which opened after the death of the frst testator within the period prescribed by law. Thus if the transmitent have not accepted the inheritance, and died after the deadline for its acceptance, hereditary transmission is not applied. In this case, it is considered that the heir refused from acceptance of inheritance by legal inaction. The study, conducted within the scope of the article, carried the inference that hereditary transmission is a tool of hereditary succession, juridical trick that provides the transfer of the inheritance from the testator to transmissar. The transfer of the right of acceptance of inheritance by way of hereditary transmission is neither a separate type of inheritance nor a case of singular succession. hereditary transmission is considered as specifc way of the exercise of the inheritance right. It is proposed to expand the subject of hereditary transmission by inclusion not only the right to accept the inheritance, which opened after the death of the frst testator, but to refuse its acceptance.

В статье исследуется сущность наследственной трансмиссии в наследственном праве Украины. Выделяются особенности механизма перехода права на принятие наследства. Рассмотрен вопрос о возможности расширения объекта наследственной трансмиссии.
The Essence of Hereditary Transmission in Inheritance Law of Ukraine
Сущность наследственной трансмиссии в наследственном праве Украины
Кухарєв, О. Сутність спадкової трансмісії у спадковому праві України / Кухарєв О. // Вісник Національної академії правових наук України. - 2015. - № 2 (81). - С. 73-81.
Keywords: Цивільне право. Civil Law. Гражданское право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; спадкове право; наследственное право; спадкування; спадкоємець; спадкодавець; спадкова трансмісія; трансмітент; трансміссар; inheriting; heirs; testator; hereditary transmission; transmitent; transmissar; наследование; наследник; наследодатель; наследственная трансмиссия; трансмитент; трансмиссар